How to Design Qualitative Research with NVivo 12 Plus for Local Government Corruption Issues in Indonesia? - Salahudin Salahudin; Achmad Nurmandi; Mohammad Jafar Loilatu (Universitas Muhammadiyah Yogyakarta, 2020)
This paper utilizes NVivo 12 Plus, a type of qualitative data analysis software, for qualitative document content analysis as a means of understanding informal fiscal policymaking practices, including bribery, corruption, collusion, lobbying, negotiation, and transactional politics. Use of NVivo 12 Plus for qualitative document content analysis facilitated the management, analysis, and visualization of data on informal fiscal policymaking. More specifically, qualitative content analysis of decisions of the Supreme Court of Indonesia revealed that informal fiscal policymaking in Malang City, Malang Regency, and Batu City, Indonesia, involved the practices of bribery, corruption, collusion, lobbying, negotiation, and transactional politics between regional leaders, bureaucrats, private actors, and political brokers. This paper contributes a qualitative research design that can be used to explain informal practices in fiscal policymaking and budget management.